Intertextuality as Depicted in Beauty and The Beast (1991) by Gary Trousdale and Kirk Wise to Belle (2021) by Mamoru Hosoda - fiska Kurniansa; Latifah Dwi Ariyani (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2023)
The study aimed to analyze the types of intertextuality shown in Beauty and the Beast (1991) to Belle (2021) by Gary Trousdale and Kirk Wise to Belle (2021) by Mamoru Hosoda, and the representation of Kristeva's intertextuality theory utilizing genotext and phenotext. The study uses the descriptive qualitative method to analyze the films Beauty and the Beast (1991) by Gary Trousdale and Kirk Wise and Belle (2021) by Mamoru Hosoda as the objective of the research. The procedure of collecting the data is watching and reading, identifying, classifying, and selecting. The procedure of analyzing the data uses Spradley's content analysis approach, with four deep stages: Domain analysis, taxonomy analysis, componential table, and cultural theme. The researcher analyzed the data by using Kristeva’s intertextuality and Fitzsimmons’s types of intertextuality. The result of the study: the types of intertextuality found in Beauty and the Beast (1991) by Gary Trousdale and Kirk Wise and Belle (2021) by Mamoru Hosoda are optional intertextuality, obligatory intertextuality, and accidental intertextuality. The most common type of intertextuality is optional intertextuality. Phenotext and genotext representations in both films are found in several characters in both films. Phenotext in utterances and scenes. Meanwhile, speech intonation and visual expressions that represent several characters as a mode of psychological response are elements of the genotext.